Impact of User Competency on Accounting Information System Success: Banking Sectors in Sri Lanka - Haleem, Athambawa Haleem; Kevin, Low Lock Teng (International Journal of Economics and Financial Issues, 2018)
Accounting Information System (AIS) provides information to managers, executives and other employees in order to take decision-making for organization success. Many organizations have different problems regarding Enterprise integrated information systems, hence when AIS implemented in banks have unintended consequences. To succeeds the AIS, user’s competency of IS is one of the major factors that influences on AIS. The purpose of research is to analyze the competency of AIS user affect the AIS success. This study used survey data from 318 respondents from eighty two banks through a structured questionnaire. Through structured equation modelling this research assessed the relationship between user competency and AIS success. Three factors from user skills named Technical, Human, and Conceptual skills and two factors from user knowledge: user knowledge and experience have contributed to AIS success. In addition, the results suggested that both user Experience and technical skills contribute more to AIS success rather than absolute values of user skills such as human skills and conceptual skills, and user knowledge. This focuses on the user perception alone rather than the objective measures of AIS success. More insights are able to obtain from this study by analyzing theoretical and empirical knowledge of user competency and AIS success. Moreover, this assists decision maker and policymakers of the organization to better understand the importance of the user competency on AIS success. The managements that are interested in implementing the new AIS in their organization may feel free to use the result as a guide to making the final decision. Keywords: Accounting information system Success, User Competency, User Skills and User Knowledge JEL Classifications: G2, M41 DOI: https://doi.org/10.32479/ijefi.7212